The Peculiarities of the Formation of the Border Guard of the Republic of Latvia: the Example of the 4th Daugavpils Border Guard Battalion (1991–1997) - Viesturs Rasnacis (Acta Humanitarica Academiae Saulensis)
After the Republic of Latvia regained its independence, the question of its border status has become essential for its security. With the creation of the Ministry of Defence, already by 13th November 1991, it immediately began the herculean task of forming proper Latvian Armed Forces. The Border Guard Forces of the Republic of Latvia was the first main force formed by the Ministry of Defence, by 2nd January 1992 there were 2,309 state positions reserved for the Border Guard units from the combined 2,452 positions at the Ministry of Defence. Out of them, 226 formed the 4th Daugavpils Border guard battalion. Its aim was to guard the Latvian border with Belarus and Lithuania. Due to its location, it eventually became the largest Border Guard battalion, additionally, by 1994 already more than 90% of border violations occurred on the checkpoints facing Belarus and Russia, therefore, putting even more pressure on the battalion. The fact that practically all of the border guards serving in the battalion spoke Russian fluently definitely was a much needed skill when dealing with contrabandists and migrants who crossed the border illegally. However, when dealing with administrative tasks, for a lot of the border guards, especially the ones coming from Russian speaking families, this proved to be quite troublesome, since they had significant problems writing the reports and other written tasks on the time set to them by their superiors. Additionally, due to the fact that the border guard service at the time was mandatory, many of those drafted against their will suffered from the lack of discipline. For most of them this was because they lacked motivation to serve adequately, they were looking for ways to easier endure their service rather than stay in the military service afterwards. Of course, this problem was not an exception for the 4th Daugavpils Border Guard battalion, this issue was common in the entirety of the Latvian Armed Forces at that time, it was the crucial location of the battalion that made this problem so troubling. Despite all of the difficulties mentioned above, the battalion, somewhat mirroring the rapid development not just of the Republic of Latvia but of all three Baltic States, advanced quite quickly and by the year 1997 it sorted most of its logistical and administrative problems. When it was transferred under the command of the Ministry of Interior, the battalion was already fully staffed and operational.